Heat Acclimation, Epigenetics, and Cytoprotection Memory. Issue 1 (10th January 2014) - Horowitz, Michal
Abstract: Heat acclimation is a within‐life phenotypic adaptation to heat. Plasticity of the thermoregulatory system is crucial for the induction of heat acclimation. In the last two decades, it has become clear that heat causes adaptive shifts in gene expression which adjust the protein balance. These changes are part of the evolvement of the acclimated phenotype. The molecular‐cellular aspects of some acclimatory mechanisms that have only been explained by physiological‐effectorial mechanisms have been discovered. This review attempts to bridge the gap between the classic physiological heat acclimation profile and the molecular/cellular mechanisms underlying the evolvement of the acclimated phenotype. Heat acclimation leads to leftward and rightward shifts in temperature thresholds of heat dissipation organs and thermal injury, respectively, thereby expanding the acclimated dynamic thermoregulatory range. Interactions between ambient temperature and afferent drives from effector organs to the hypothalamic thermoregulatory center with modifications in warm/cold sensitive neuron ratio and excitability contribute to the threshold changes. The altered threshold for thermal injury is associated with progressive enhancement of inducible cytoprotective networks, including HSP70, HSF1, and HIF‐1α. These molecules are also important in acclimatory kinetics. Aspects of cross‐adaption, cross‐tolerance and interference with heat acclimation are explained using molecular‐cellular physiological interactions, with the heart, skeletal muscles, and water secretory glands as models. Lastly, the roles of epigenetic mechanisms in transcriptional regulation during induction of the acclimated phenotype, its decay, and reinduction are discussed. Posttranslational histone modifications in the promoters of hsp70 and hsp90 form part of our prototype model of heat‐acclimation‐mediated cytoprotective memory. © 2014 American Physiological Society. Compr Physiol 4:199‐230, 2014.